THE PHYSICO-CHEMICAL PROPERTIES OF A SUBDUCTED SLAB FROM GARNET ZONATION PATTERNS (SESIA ZONE, WESTERN ALPS) - Konrad-Schmolke M.; Babist J.; Handy M.R.; O'Brien P.J. (My University, 2006)
Garnets in continentally derived high-pressure (HP) rocks of the Sesia Zone (Western Alps) exhibit three different chemical zonation patterns, depending on sample locality. Comparison of observed garnet zonation patterns with thermodynamically modelled patterns shows that the different patterns are caused by differences in the water content of the subducted protoliths during prograde metamorphism. Zonation patterns of garnets in water-saturated host rocks show typical prograde chemical zonations with steadily increasing pyrope content and increasing XMg, together with bell-shaped spessartine patterns. In contrast, garnets in water-undersaturated rocks have more complex zonation patterns with a characteristic decrease in pyrope and XMg between core and inner rim. In some cases, garnets show an abrupt compositional change in core-to-rim profiles, possibly due to water-undersaturation prior to HP metamorphism. Garnets from both water-saturated and water-undersaturated rocks show signs of intervening growth interruptions and core resorption. This growth interruption results from bulk-rock depletion caused by fractional garnet crystallization. The water content during burial influences significantly the physical properties of the subducted rocks. Due to enhanced garnet crystallization, water-undersaturated rocks, i.e. those lacking a free fluid phase, become denser than their water-saturated equivalents, facilitating the subduction of continental material. Although water-bearing phases such as phengite and epidote are stable up to eclogite-facies conditions in these rocks, dehydration reactions during subduction are lacking in water-undersaturated rocks up to the transition to the eclogite facies, due to the thermodynamic stability of such hydrous phases at high P-T conditions. Our calculations show that garnet zonation patterns strongly depend on the mineral parageneses stable during garnet growth and that certain co-genetic mineral assemblages cause distinct garnet zonation patterns. This observation enables interpretation of complex garnet growth zonation patterns in terms of garnet-forming reactions and water content during HP metamorphism, as well determination of detailed P-T paths. © 2006 Oxford University Press.
Keywords: DEHYDRATION; HIGH-PRESSURE METAMORPHISM; SESIA ZONE; SUBDUCTION; THERMODYNAMIC MODELLING